Analysis of Analysis of Financial Performance in Gulingan Village, Mengwi Subdistrict, Badung Regency - Ni Luh Putu Sandrya Dewi; Putu Diah Kumalasari; Ni Luh Putu Widhiastuti (JUSTBEST Journal of Sustainable Business and Management, 2026)
This study aims to analyze the financial performance of Gulingan Village, Mengwi Subdistrict, Badung Regency, by measuring financial ratios based on the 2023–2025 Village Revenue and Expenditure Budget Implementation Report (APBDes). The research method used is quantitative descriptive, with data sources consisting of budget implementation reports and interview results. The analysis was conducted using the self-reliance ratio, effectiveness ratio, efficiency ratio, activity ratio, and growth ratio. The results indicate that Gulingan Village’s self-reliance ratio falls into the very low category, with a value of 0% in 2023 and 2024 and 6% in 2025, indicating a high level of dependence on government transfer funds. The effectiveness ratio showed fairly effective performance in 2023 (62%) and improved to effective in 2024 (100%) and 2025 (95%). The efficiency ratio fell into the efficient to highly efficient category with values of 78%, 71%, and 69%, respectively. The activity ratio indicates optimal allocation of operating expenditures and capital expenditures in the moderate category. Meanwhile, the revenue growth ratio fluctuates with negative growth in the 2022–2023 and 2024–2025 periods, while expenditure growth shows a high category in the 2022–2024 period and declines in the 2024–2025 period. Overall, the financial management of Gulingan Village has been effective and efficient; however, the village’s financial self-reliance remains low, necessitating efforts to optimize Village Owned Revenue (PADes) to reduce dependence on transfer funds.